Transportation Visibility Platform in a Complex Supply Chain - Slawomir Wycislak (International Journal of Supply Chain Management, 2020)
There is a gap between expectations on benefits from supply chain visibility and successfully implemented case studies. The significant barriers to visibility are created rather by not technological factors. The article focuses on identifying patterns emerged from dynamics of relationships within a supply chain during deployment of transportation visibility platform.